A further insight into the practical applications of exopolysaccharides from Sclerotium rolfsii - Viñarta, Silvana Carolina (2006)
The ability of exopolysaccharides EPS I (after 48 h-cultivation) and EPS II (after 72 h-cultivation), produced by the fungus Sclerotium rolfsii ATCC 201126, to minimize the liquid separation (syneresis) experienced by cooked starch pastes during refrigeration was investigated. After comparing different techniques, the extent of syneresis was finally estimated by daily measurement of the liquid phase length (Δh) separated above the sedimented phase throughout the storage at 5 °C. The degree of syneresis was represented by Δh/h0, where h0 stands for the initial height of the sample dispersion. Proportions varying between 9.90/0.10 and 9.00/1.00 (w/w) for 2% (w/v) corn starch/EPS aqueous blends were evaluated against 2% (w/v) corn starch (CS) as control. Up to 20 days of refrigeration and for the highest tested proportion (9.00/1.00), syneresis could be completely inhibited or 91% reduced by EPS II and EPS I, respectively. EPS II was thereby selected as the optimal syneresis preventive and subsequent analysis of its rheological behaviour in distilled water, skimmed and whole milk confirmed the ability to increase viscosity with a non-Newtonian, pseudoplastic behaviour. Rheology of CS/EPS II blends, when compared to the separated CS and EPS II, also evidenced a desirable synergistic effect in the aforementioned solvents, as witnessed by the increase in viscosity, higher consistency coefficients and lower flow behaviour indexes. Additionally, EPS II was able to prevent syneresis without affecting pH, gelling properties, hardness or colour. These results revealed that scleroglucan might become a food-approvable hydrocolloid with prospective use as food stabilizer and water loss preventive.